Indigenous data and policy in Aotearoa New Zealand - Sporle, Andrew; West, Kiri; Hudson, Maui (Routledge, 2020)
This chapter tracks the development of Te Mana Raraunga, the Māori Data Sovereignty Network and the influence it has had alongside the Data Iwi Leaders Group in establishing Māori data sovereignty as a legitimate policy discourse within Aotearoa New Zealand. It outlines the key definitions, frameworks and tools that have been developed and are being utilized by agencies and institutions as Māori communities look to increase Māori control of Māori data.

Understanding Māori Rights and Interests in Intellectual Property arising from Research and Innovation - Sterling, Rogena; Riddle, KatieLee; Brooks, Robert Tūrongo; Hudson, Maui (Te Kotahi Research Institute, 2021)
Keywords: indigenous data sovereignty; intellectual property

Intellectual Property, Mātauranga Māori - Sterling, Rogena; Riddle, KatieLee; Tūrongo Brooks, Robert; Anderson, Jane; Hudson, Maui (Te Kotahi Research Institute University of Waikato, 2021)
This literature review has been conducted to consider the various national legislation and international agreements that comprise New Zealand’s Intellectual Property Rights (IP) regime. It will evaluate if and how such legislation and agreements protect and enable Māori IP rights and interests with respect to Māori data, genomic data and mātauranga Māori. The review also identifies some mechanisms that might also enhance Māori control of these types of data. The Westminster approach of legislation in New Zealand and its approach to IP protection based on Copyrights, Patents and Trade Marks are juxtaposed against traditional Maori approaches of communally held ancestral knowledge (mātauranga) passed down through generations (whanaungatanga) based on guardianship and protection (kaitiakitanga) and the self-determination of use of such knowledge (rangatiratanga). Attempting to align tikanga concepts to the Westmionster model of law is challenging as the two share completely different notions of ownership and responsibility. Expectations of protection, to prevent misappropriation and commercialisation by non- Māori of mātauranga Māori and Māori data, extend beyond the parameters of existing IP law, creates a similar disjunct. Genomic Research generates data, some of which can be protected by IP, however researchers working with genetic/genomic data from taonga species have often failed to acknowledge the non-IP interests of Maori. As a result, Maori have taken it upon themselves to advocate for their rights to data through Māori data sovereignty discourse as well as create guidelines for culturally appropriate genomic research with explicit references to data security and management (e.g. Te Mata Ira, Te Nohonga Kaitiaki). Other extra-legal options, such as Biocultural Labelling to alert users where particular data has Māori rights and/or interests, are emerging to maintain create durable provenance data and connect next users of data with the responsible Indigenous communities. Though the intellectual property regime in New Zealand may provide some protections, there are still significant areas where the legal system does not provide sufficient protections for Māori data, taonga species and mātauranga. The UN Declaration on the Rights of Indigenous Peoples provides a framework of international support for Indigenous rights, but local government and other home-grown mechanisms are important to enable Māori governance of data. Local approaches Māori Data Sovereignty and Māori Data Governance afford Maori the opportunity to be directly involved as kaitiaki of their mātauranga and assert rangatiratanga over data and its use.
Keywords: indigenous data; intellectual property; mātauranga māori

Empowering Equitable Data Use Partnerships and Indigenous Data Sovereignties Amid Pandemic Genomics - Haring, Rodney C.; Blanchard, Jessica W.; Korchmaros, Josephine D.; Lund, Justin R.; Haozous, Emily A.; Raphaelito, Josie; Hudson, Maui; Tsosie, Krystal S. (Frontiers in Public Health, 2021)
The COVID-19 pandemic has inequitably impacted Indigenous communities in the United States. In this emergency state that highlighted existing inadequacies in US government and tribal public health infrastructures, many tribal nations contracted with commercial entities and other organization types to conduct rapid diagnostic and antibody testing, often based on proprietary technologies specific to the novel pathogen. They also partnered with public-private enterprises on clinical trials to further the development of vaccines. Indigenous people contributed biological samples for assessment and, in many cases, broadly consented for indefinite use for future genomics research. A concern is that the need for crisis aid may have placed Indigenous communities in a position to forego critical review of data use agreements by tribal research governances. In effect, tribal nations were placed in the unenviable position of trading short-term public health assistance for long-term, unrestricted access to Indigenous genomes that may disempower future tribal sovereignties over community members' data. Diagnostic testing, specimen collection, and vaccine research is ongoing; thus, our aim is to outline pathways to trust that center current and future equitable relationship-building between tribal entities and public-private interests. These pathways can be utilized to increase Indigenous communities' trust of external partners and share understanding of expectations for and execution of data protections. We discuss how to navigate genomic-based data use agreements in the context of pathogen genomics. While we focus on US tribal nations, Indigenous genomic data sovereignties relate to global Indigenous nations regardless of colonial government recognition.
Keywords: indigenous data sovereignty

Rights, interests and expectations: Indigenous perspectives on unrestricted access to genomic data - Hudson, Maui; Garrison, Nanibaa’ A.; Sterling, Rogena; Caron, Nadine R.; Fox, Keolu; Yracheta, Joseph; Anderson, Jane; Wilcox, Phil; Arbour, Laura; Brown, Alex; Taualii, Maile; Kukutai, Tahu; et al. (Nature Reviews Genetics, 2020)
Addressing Indigenous rights and interests in genetic resources has become increasingly challenging in an open science environment that promotes unrestricted access to genomic data. Although Indigenous experiences with genetic research have been shaped by a series of negative interactions, there is increasing recognition that equitable benefits can only be realized through greater participation of Indigenous communities. Issues of trust, accountability and equity underpin Indigenous critiques of genetic research and the sharing of genomic data. This Perspectives article highlights identified issues for Indigenous communities around the sharing of genomic data and suggests principles and actions that genomic researchers can adopt to recognize community rights and interests in data.
Keywords: crown law; data sovereignty; ethics; genes; genetic databases; genomic sequencing; population genetics